Formulasi Sabun Mandi Cair Berbasis Virgin Coconut Oil (VCO): Optimalisasi Pemanfaatan Produk Lokal Untuk Perawatan Kulit dan Pencegahan Dehidrasi - Maulina, Novia; Muslikh, Faisal Akhmal; Nastiti, Ginanjar Putri; Fadilla, Rahma Nur; Winayah, Mesri Ananta; Kamelin, Badira; Firdaus, Natasya Octavia Putri; Fricananta, Salma Salsabila; Dewi, Tanaya Jati Dharma (Bioscientist : Jurnal Ilmiah Biologi, 2025)
Skin dehydration is a common issue affecting 40–50% of the adult population, resulting in dry, rough, and dull skin, as well as itching, irritation, and premature aging. The "back to nature" trend has increased interest in natural skincare products that are more environmentally friendly and gentler on the skin. Virgin coconut oil (VCO) is a popular natural ingredient known for its ability to maintain skin moisture and provide protection. This study aims to develop a liquid soap formulation using VCO to address skin dehydration. The research methods included formulation and evaluation of liquid soap through organoleptic testing, foam stability, specific gravity, pH, as well as hedonic and irritation tests. The results showed that: (1) Formula III met all physical evaluation parameters, including organoleptic characteristics, foam stability and height, specific gravity, and pH, in accordance with SNI standards; (2) Formula III was the most preferred by panelists in the hedonic test and caused no skin irritation based on irritation test results. Therefore, Formula III can be concluded as the optimal formulation for VCO-based liquid bath soap.